Development of a grilling and herbal steam device for Thai traditional medicine - Kaensom, Saksri; Kaensom, Parichart; Sirimaskasem, Thanyaphob; Boonraksa, Promphak (International Journal of Innovative Research and Scientific Studies, 2025)
This research focuses on developing a herbal grill and steamer for health enhancement. The objectives of this work are to construct and test the efficiency of the herbal grill and steamer that enhance the health of the Khao Na Tad Moo 12 community enterprise group, Lam Narai Subdistrict, Chai Badan District, Lop Buri Province, Thailand, which is located in the central region of Thailand. The research results found that the usage patterns of the herbal grill and steam machine consist of two patterns. Pattern 1 uses the herbal grill and steam machine twice for 15 minutes each, then sits and rests for 5 minutes, for a total of 35 minutes. Pattern 2 sets the temperature at 40 degrees Celsius and uses the herbal steam machine for a total of 20 minutes, once. Both patterns maintain a temperature of 37 to 46 degrees Celsius. The wooden floor of the grill machine is made from natural pine wood. It measures 90 centimeters wide, 195 centimeters long, and 67 centimeters high. The herbal steam tent is made of 10 mm stainless steel, 99 centimeters in diameter, and 110 centimeters high. The entrance is 54 centimeters wide. The results of the efficiency test of the herbal grill, Model 1, show an average maximum temperature of 43.83 degrees Celsius and an average minimum temperature of 39.00 degrees Celsius. Model 2 has an average maximum temperature of 41.97 degrees Celsius and an average minimum temperature of 39.00 degrees Celsius. The results of the efficiency test of the herbal steam tent, Model 1, show an average maximum temperature of 45.94 degrees Celsius and an average minimum temperature of 33.31 degrees Celsius. Model 2 has an average maximum temperature of 41.83 degrees Celsius and an average minimum temperature of 38.06 degrees Celsius.